New Technologies in Crisis Management - Marciniak, Dominika; Szymaniec-Mlicka, Karolina; Kelm, Hanna (Journal of Public Governance, 2023)
Objective: Modern technologies are increasingly important in managing a public organisation. This also applies to the very sensitive area of crisis management, the effectiveness of which directly affects the health and lives of citizens. This article aims to analyse the literature on the subject of the use of modern technologies in crisis management.Research Design & Methods: The article uses literature review as a research method.Findings: The analysis of the obtained results indicates that the use of modern technologies in crisis management is a current research topic. At the same time, the application layer shows the potential of using modern technologies.Implications/Recommendations: Future research should focus on determining the acceptance of modern technology in the organisation. At the same time, it seems important to analyse the conditions for the optional implementation of modern solutions in the organisation.Article classification: theoretical/review paperJEL classification: H7